1995
DOI: 10.1093/nar/23.17.3594
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of c-myconcogene expression by a polyamine-complexed triplex forming oligonucleotide in MCF-7 breast cancer cells

Abstract: Polyamines are excellent stabilizers of triplex DNA. Recent studies in our laboratory revealed a remarkable structural specificity of polyamines in the induction and stabilization of triplex DNA. 1,3-Diaminopropane (DAP) showed optimum efficacy amongst a series of synthetic diamines in stabilizing triplex DNA. To utilize the potential of this finding in developing an anti-gene strategy for breast cancer, we treated MCF-7 cells with a 37mer oligonucleotide to form triplex DNA in the up-stream regulatory region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 40 publications
0
45
0
1
Order By: Relevance
“…These include the covalent attachment of the duplex intercalator, pyrene, to the end of the oligonucleotide (along with sugar modification at the 2Ј position) or the incorporation of a phosphoramidate backbone consisting of substitution of a nitrogen for the 3Ј-bridging oxygen (31,45). Another approach to stabilize triplexes (and to aid entry into cells) is the use of polyamines either covalently attached to the TFOs or used in conjunction with the oligonucleotides during transfection (46,47).…”
mentioning
confidence: 99%
“…These include the covalent attachment of the duplex intercalator, pyrene, to the end of the oligonucleotide (along with sugar modification at the 2Ј position) or the incorporation of a phosphoramidate backbone consisting of substitution of a nitrogen for the 3Ј-bridging oxygen (31,45). Another approach to stabilize triplexes (and to aid entry into cells) is the use of polyamines either covalently attached to the TFOs or used in conjunction with the oligonucleotides during transfection (46,47).…”
mentioning
confidence: 99%
“…There have been several reports describing the use of triplex-forming oligonucleotides to inhibit the expression of endogenous genes (12)(13)(14)(15)(16)(17). However, none of these reports provided direct evidence for the implication of triplex formation at the target site in the inhibitory activity.…”
mentioning
confidence: 99%
“…Compared to antisense ODNs, an additional restriction to potential target sequences for triplex formation is linked to chromatin structure, a parameter which is largely unknown for most of potential target sequences. Endogenous gene silencing by TFOs has been demonstrated in many studies (372,374,375,392,393), which suggests the accessibility of nuclear DNA for TFOs. However, in these studies, triplex formation with DNA in native chromatin structure was not unambiguous confirmed.…”
Section: 33mentioning
confidence: 98%
“…In lymphocytes, HIV-1 transcription was inhibited by (G, T)-rich 38-mer TFOs directed against the transcription initiation or nuclear factor Sp1 binding sites (372), This effect may be due to a direct interaction between the HIV-1 integrase and TFOs (307). In many studies, gene inhibition of the c-myc oncogene by TFOs is ascribed to triplex formation (373)(374)(375). However, other mechanism may also be possible since titration of the transcription activator CNBP by the purine-rich ODN could fully account for the observed decrease in c-myc transcription (376,377).…”
Section: Gene Regulation Bymentioning
confidence: 99%